IDENTIFIKASI LETAK DAN JENIS SESAR BERDASARKAN METODE GAYABERAT SECOND VERTICAL GRADIENT STUDI KASUS SESAR LEMBANG, KOTA BANDUNG, JAWA BARAT - M Wildan Firdaus; Agus Setyawan; Mahmud Yusuf (Youngster Physics Journal, 2016)
Gravity measurement has been done in Lembang area, Bandung on 2014. Measurement were perform with relative gravity (Scintrex CG-5) with 28 measuring point around Lembang fault. The aim of this research is to observe gravity response Bouguer anomali toward Lembang fault structure along 22 kilometers from eastern to west. In this research, we use second vertical gradient to known about the location and kind of fault structure. As the result from this research shown the Bouguer anomali has a distribution value around -2 mGal – 52 mGal, this result indicated that Lembang Fault are located between high and low Bouguer anomali. While the result from second vertical gradient indicated that Lembang Fault is a normal fault.Keywords: gravity, Bouguer, SVG, fault, Lembang